Hydropower and environmental sustainability: A holistic assessment using multiple biophysical indicators - Andrei Briones-Hidrovo (Elsevier, 2021)
Along with other low-carbon combustion-free energy sources, hydropower is considered a valuable tool for mitigating the current climate and ecological crisis and achieve environmental sustainability. However, it is still unclear to what extent hydropower is or not environmentally sustainable. The literature reveals i) that no truly holistic assessments have been carried out and ii) that there are contradictory results and conclusions. The present study addresses this gap by conducting a holistic assessment, using eight biophysical indicators of different approaches, and taking two different hydropower plant schemes as study cases. The results of the assessment show that the run-of-river hydropower plant study case is by far more environmentally sustainable than the dam hydropower plant scheme. As hydropower schemes and sizes vary, it is highlighted the importance of including as many indicators as possible to ensure broader and complete assessments and the avoidance of bias in the conclusions and ease comparison with other low-carbon combustion-free energy sources and their technologies. Moreover, the present study addresses how and within which parameters the environmental sustainability of hydropower is usually determined. The complementary set of indicators provided here, which have different scope and complexity, could be adopted for improving future decision-making in energy policies and specifically for hydropower.